Why is the gamma function so as it is? - Gronau, Detlef (Teaching Mathematics and Computer Science, 2003)
This is a historical note on the gamma function Γ. The question is, why is Γ(n) for naturals n equal to (n−1)! and not equal to n! (the factorial function n! = 1·2 · · · n) ? Was A. M. Legendre responsible for this transformation, or was it L. Euler? And, who was the first who gave a representation of the so called Euler gamma function?